Exploring the Role of Progression Free Survival in Chemotherapy Protocol: A Literatur Review: Telaah Pustaka Penilaian Progression Free Survival Sebagai Parameter Klinis Tata Terapi Kanker - Padirja, Shyfa Anindya; Rahayu, Ngesti; Fitria, Tisa; Fasya, Saniya Puspa; Umma, Nafa; Zahrah, Salsabila Salma; Santoso, Setiyo Budi (Prosiding University Research Colloquium, 2024)
Progression-Free Survival (PFS) measures cancer patients’ resistance to tumor progression. This alternative measurement is effective in assessing the performance of cancer therapy protocols and may serve an evidence for evaluating the quality of life of patients and planning follow-up treatments. Here in, we review a number of PFS data publications for drugs used in cancer therapy. The review involves ten scientific articles met the inclusion criteria provided by the PubMed database. Our finding present the optimal performance of chemotherapy protocols in preventing disease progression in seven various cancer populations. The highest PFS values for each cancer such as: crizotinib for lung cancer (28.71 months), enzalutamide for prostate cancer (7.1 months), pamiparib for stomach cancer (3.7 months), anlotinib for liver cancer (4.2 months), irinotecan plus raltitrexed for esophageal cancer (3.91 months), folfoxiri plus bevacizumab for metastatic colorectal cancer (10.7 months), and paclitaxel plus vistusertib for ovarian carcinoma (4.5 months).